Perovskite-Like Carbodiimides AB(NCN)3: Synthesis and Characterization of MnHf(NCN)3 and FeHf(NCN)3 - Bourakhouadar, Hicham; Hempelmann, Jan; van Leusen, Jan; Drichel, Andreas; Bayarjargal, Lkhamsuren; Koldemir, Aylin; Reimann, Maximilian Kai; Pöttgen, Rainer; Slabon, Adam; Corkett, Alex J.; Dronskowski, Richard (Journal of the American Chemical Society, 2024)
Two novel ternary air-stable transition-metal carbodiimides, MnHf(NCN)3 and FeHf(NCN)3, were synthesized via solid-state metathesis using either ZnNCN or Na2NCN as the carbodiimide source and the corresponding binary metal chlorides. These two phases are the first examples of transition-metal carbodiimides with an AB(NCN)3 composition, akin to ubiquitous ABO3 perovskite oxides. The crystal structure of MnHf(NCN)3 was determined and refined from powder X-ray diffraction (XRD) data in the non-centrosymmetric space group P6322 allowing for chirality, the assignment of which is supported by second-harmonic generation (SHG) measurements. FeHf(NCN)3 was found to crystallize isotypically, and the presence of iron(II) in a high spin state was confirmed by 57Fe Mößbauer spectroscopy. The structures are revealed to be NiAs-derived and can be described as a hexagonal stack of NCN2– anions with metal cations occupying 2/3 of the octahedral voids. Both IR spectroscopic measurements and DFT calculations agree that the NCN2– unit is a bent carbodiimide with C 2v symmetry, necessary to account for the size difference present in such a vacancy-ordered structure. Magnetic studies reveal predominantly strong antiferromagnetic interactions but no long-range order between the paramagnetic Mn2+ centers, likely due to the dilution of Mn2+ over the octahedral sites or perhaps even due to some degree of magnetic frustration. The optical and electrochemical properties of MnHf(NCN)3 were then studied, revealing a wide band gap of 3.04 eV and p-type behavior.